2010
DOI: 10.1111/j.1467-985x.2009.00629.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Publication Bias in Meta-Analyses in the Presence of Between-Study Heterogeneity

Abstract: Between-study heterogeneity and publication bias are common features of a meta-analysis that can be present simultaneously. When both are suspected, consideration must be made of each in the assessment of the other. We consider extended funnel plot tests for detecting publication bias, and selection modelling and trim-and-fill methods to adjust for publication bias in the presence of between-study heterogeneity. These methods are applied to two example data sets. Results indicate that ignoring between-study he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
123
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(124 citation statements)
references
References 35 publications
1
123
0
Order By: Relevance
“…This can be formally confirmed by means of a homogeneity test using a commonly used "Q-statistic" (Engels et al 2000). The Q-statistic (computation as in Peters et al 2010) tests if the primary studies share a common effect size and whether an FE estimate is relevant to the analysis (Poot 2014). After combining K effect sizes, if the resulting Q-statistic from this homogeneity test is greater than the upper-tail critical value of the chi-square distribution with K − 1 degrees of freedom, then the variance in effect sizes obtained from the primary studies is significantly greater than what can be observed due to random variation around a common effect size (Shadish, Haddock 1994).…”
Section: Advocacymentioning
confidence: 92%
“…This can be formally confirmed by means of a homogeneity test using a commonly used "Q-statistic" (Engels et al 2000). The Q-statistic (computation as in Peters et al 2010) tests if the primary studies share a common effect size and whether an FE estimate is relevant to the analysis (Poot 2014). After combining K effect sizes, if the resulting Q-statistic from this homogeneity test is greater than the upper-tail critical value of the chi-square distribution with K − 1 degrees of freedom, then the variance in effect sizes obtained from the primary studies is significantly greater than what can be observed due to random variation around a common effect size (Shadish, Haddock 1994).…”
Section: Advocacymentioning
confidence: 92%
“…If the latter is the case, the trim-andfill-adjusted effect size may be underestimating the true effect size (e.g., Peters, Sutton, Jones, Abrams, & Rushton, 2007). Unfortunately, the proposed methods of unconfounding publication bias and moderating factors (e.g., conducting funnel plot analyses within a subgroup of studies) are applicable only to large meta-analyses (see Peters et al, 2010).…”
Section: Stimulant Effects On Healthy People's Delayed Episodic Memorymentioning
confidence: 99%
“…We thus suggest that methods such as the trim and fill can be used along with selection models, cumulative meta-analysis, or other methods under varying conditions in simulation studies. Furthermore, simulation studies could consider whether the nature and/or form of the heterogeneity (Peters et al, 2010) affect publication bias results. Such studies can also explore whether relative indices (e.g., I…”
Section: Limitations and Recommendationsmentioning
confidence: 99%